High-resolution environmental reconstruction in SW Peloponnese, Greece, covering the last c. 6000 years: Evidence from Agios Floros fen, Messenian plain. (February 2016) - Katrantsiotis, Christos; Norström, Elin; Holmgren, Karin; Risberg, Jan; Skelton, Alasdair
A paleolimnological record from the central Messenian plain (southwestern Peloponnese, southern Greece) indicates rapid changes in the water level and chemistry of a transient lake on the flanks of the Taygetos Mountains during the last c . 6000 years. The analyses are based on diatoms as well as carbon and nitrogen isotopes from bulk sediments in a 7.5-m-long sediment core retrieved from the drained fen of Agios Floros, at the northern banks of the ancient River Pamisos. The sequence consists of fen peat in the uppermost section underlain by lacustrine sediments, which are punctuated by two layers of clay with diatomaceous silt bands. High accumulation rate is recorded in the oldest part of the section (up to 23 mm/yr), particularly during two decadal-long periods centered at c . 5700 and c . 5300 cal. BP. The diatom record reveals pronounced peaks in the planktonic taxon Cyclotella distinguenda, which correspond to the laminated sequences, reflecting the rapid development of a deep lake with an open water environment during these two time periods. Another two events with intermediate water levels are inferred at c . 5200 and c . 4600 cal. BP. These short-lived phases were probably, to a large extent, caused by local tectonic processes and the consequent hydrological anomalies of the nearby karst springs, although abrupt climatic changes with enhanced precipitation might have also played a role. At c . 4500 cal. BP, our data suggest the development of terrestrial conditions in this area, which can be attributed to the decreasing activity/dry up of springs, probably associated with more arid climate. After c . 2500 cal. BP, the diatom record infers a return to wetter conditions, probably as a response to more humid climate with marked seasonality and human activities, developing the present-day environment with cultivated and seasonally semi-flooded fields.